#1**+1 **

Simplify the following:

(-20)/(-5) - (57 + 6)/(-9)

Reduce (-20)/(-5) to lowest terms. Start by finding the GCD of -20 and -5.

The gcd of -20 and -5 is -5, so (-20)/(-5) = (-5×4)/(-5×1) = (-5)/(-5)×4 = 4:

4 - (57 + 6)/(-9)

Evaluate 57 + 6 using long addition.

Reduce 63/(-9) to lowest terms. Start by finding the GCD of 63 and -9.

The gcd of 63 and -9 is 9, so 63/(-9) = (9×7)/(9 (-1)) = 9/9×7/(-1) = 7/(-1):

4 - 7/(-1)

Simplify the sign of 7/(-1).

Multiply the numerator and denominator of 7/(-1) by -1:

4 - -7

Multiply all instances of -1 in -(-7).

(-1)^2 = 1:

4 + 7

**=11**

Guest Sep 16, 2018